The Effect of the Industrial Production Index (IPI) on the Indonesian Sharia Stock Index (ISSI) During the COVID-19 Pandemic Period 2020–2023 - Abi Suar; Yetty Yetty; Nurdin I Muhammad; Nonce Hasan; Abdurrahman Senuk; Ririn Damayanti (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The Industrial Production Index (IPI) is an indicator that reflects the condition of industrial production within a country. In the Indonesian capital market, the IPI consists of stock movements listed on the Indonesia Stock Exchange (IDX) that are incorporated into an index known as the Industrial Production Index. An improvement in the IPI reflects favorable conditions in the country’s industrial economy. In general, an increase in the IPI is also expected to affect other indices, particularly the Indonesian Sharia Stock Index (ISSI). This study employed a quantitative approach using the Vector Auto Regression (VAR) as analytical tools. The objective of this research was to examine the determinants of the Industrial Production Index on the Indonesian Sharia Stock Index during the COVID-19 pandemic period. The findings indicate that, in the short term, the IPI had a negative and significant effect on the Indonesian Sharia Stock Index. Furthermore, the results of the Impulse Response Function (IRF) analysis reveal that the ISSI variable responded negatively to shocks generated by the IPI variable from the beginning to the end of the observation period, indicating a permanent negative response. Therefore, during the COVID-19 pandemic in Indonesia, the IPI did not exert a positive influence on the ISSI.